PERSEPSI MAHASISWA IAIN PADANGSIDIMPUAN TERHADAP PEMBELAJARAN ONLINE DI ERA PANDEMI COVID-19 - Maulana Arafat Lubis; Nisha Marina; Nashran Azizan; Fery Muhamad Firdaus (IAIN Padangsidimpuan, 2021)
Many impacts occurred when the COVID-19 pandemic occurred to disturb all humans on earth. The unrest came from students. One of the student concerns was that learning was carried out online. This case is the basis of the research. The research objective was to explore student difficulties during online learning during the COVID-19 period, the application used during online learning during the COVID-19 period, and the student's response to online learning during COVID-19. This study uses a qualitative method through a case study approach. The research was conducted at IAIN Padangsidimpuan. The informants in this study were 37 PGMI students from 2016-2019. Data collection using unstructured-planned interviews. The research procedure refers to the Creswell model. Data analysis used ATLAS.ti version 8 software. The results of this study obtained information from informants that students experienced many difficulties during online learning during the COVID-19 period, such as the high cost of buying data packages, the problem of internet signals and the exposure of less understood lecturers' material. During online learning, the teleconference application often used is google meet, while the social media that is always used is WhatsApp. So, from the conscience of each informant, they hoped that the learning process would not be thoroughly carried out online to reduce costs for buying internet packages or learning to be carried out face-to-face again on the condition that they adhere to health protocols.